Role of the composition and preparation method in the activity of hydrotalcite-derived Ru catalystin the catalytic partial oxidation of methanes - Ballarini, Adriana Daniela (2013)
Hydrotalcite-derived Ru catalysts were tested in the catalytic partial oxidation of CH4 to produce syngas. The effect of Ru content, oxidic matrix composition, and preparation procedure on chemicalephysical properties and performances of catalysts was studied. Bulk catalysts (0.25 and 0.50 wt.% Ru) were obtained via Ru/Mg/Al hydrotalcite-type (HT) precursors with carbonates or silicates as interlayer anions. A supported catalyst was prepared by impregnation on a calcined Mg/AleCO3 HT. Ru/g-Al2O3 was evaluated for comparison. Both the Ru dispersion and the interaction with the support decreased as the Ru loading increased and when silicates were present due to RuO2 segregation. Regardless of the Ru loading, carbonate-derived catalysts performed better than those containing silicates. The increased Ru loading improved the initial activity, but deactivation occurred after high temperature tests. Stability tests for shorter contact times over a 0.25 wt.% bulk sample obtained from Ru/Mg/Al HT with carbonates showed a tendency to deactivate at 750 C.